Review of Cultural Translation and Knowledge Transfer on Alternative Routes of Escape from Nazi Terror Meditations through Migration, Edited by Susanne Korbel and Philipp Strobl, ISBN: 978-0-367-56911-2, Routledge. 2022. - Mehrdad Vasheghani Farahani (Media and Intercultural Communication: A Multidisciplinary Journal)
During the dark retinue of Nazi (1933-1945) in Germany, many innocent people lost their lives, and many were forcibly exiled from their home countries (Bazyler & Alford, 2007 & Mayda, 2010). This unwanted upsurge of immigration resulted in the clash of different cultures and languages. New immigrants’ adaptation to the host culture(s) remains a contentious hence uncharted line of research. The key question at stake is how refugees deal with ethnic, religious, and cultural affiliations in their target destinations and how they portray knowledge transfer and cultural translations.